A people's history of the Russian Revolution - Faulkner, Neil (Left Book Club, 2017)
The Russian Revolution may well be the most misunderstood event in modern history. In A People's History of the Russian Revolution, Neil Faulkner sets out to debunk the myths. In this fast-paced introduction to the tumultuous events, the Russian people are the heroes. Faulkner shows how a mass movement of millions, organised in democratic assemblies, mobilised for militant action, destroyed a regime of landlords, profiteers and warmongers. He rejects caricatures of Lenin and the Bolsheviks as authoritarian conspirators, 'democratic-centralists' or the progenitors of Stalinist dictatorship. He argues that the Russian Revolution was an explosion of democracy and creativity - and that it was crushed by bloody counter-revolution and replaced with a monstrous form of bureaucratic state-capitalism. Laced with first-hand testimony, this history seeks to rescue the democratic essence of the revolution from its detractors and deniers, offering a perfect primer for the modern reader.